(untitled) (East West Medical College Journal, 2026)
Fibrous dysplasia (FD) is a benign medullary fibro-osseous anomaly that compromises the mechanical strength of bones, especially the long bones that bear strong mechanical stresses. It can lead to an inability to remodel immature bone into mature lamellar bone, resulting in inappropriate bone alignment in response to mechanical stresses. Case Summary : A 17-year-old male presented with a 2-month history of persistent right hip pain and normal gait, without any neurological symptoms in the limbs or trunk. Physical examination revealed tenderness over the right hip, with normal sensory, motor, and reflex findings. Imaging studies demonstrated a “ground-glass” appearance, cortical scalloping, and expansion involving the right proximal femur and femoral neck, consistent with fibrous dysplasia. A pathological fracture of the right proximal femur was also noted. Surgical intervention was planned based on clinical and radiological findings. Conclusion: Surgeons can successfully treat fibrous dysplasia in the upper femur by using a bone allograft secured with a trochanteric plate. After surgery, the care team should keep a close watch through frequent follow up and routine X-rays to confirm solid healing and catch any new problems early. EWMCJ Vol. 14, No. 1, January 2026: 87-90